The effect of alternate wetting and severe drying irrigation on grain yield and water use efficiency of Indica‐japonica hybrid rice (Oryza sativa L.). (5th June 2018) - Chu, Guang; Chen, Tingting; Chen, Song; Xu, Chunmei; Wang, Dangying; Zhang, Xiufu
Abstract: Identification of a rice cultivar with high yield potential has been heavily sought by researchers in China, and pursuant to this goal, several indica‐japonica hybrid rice (IJHR) cultivars have been studied for over a decade. However, in addition to high yield, it is important that the cultivar also exhibit good water use efficiency (WUE). This study compared the yield performance and WUE of the IJHR cultivars under alternate wetting and severe drying (AWSD) irrigation regimen to the japonica inbred rice (JIR) cultivars. Field experiments were conducted on two representative IJHR cultivars (Chunyou927 and Yongyou538) and two representative JIR cultivars (Xiushui09 and Zhejing99) in 2015 and 2016 with two different irrigation methods: continuous flooding (CF) and AWSD. Irrigation water was 275–349 mm in the AWSD irrigation regimen, which was 49.8%–56.2% of that (552–620 mm) applied to the CF irrigation regimen. Compared to CF, the AWSD irrigation method significantly decreased grain yield in both IJHR and JIR cultivars, with a more significant reduction in JIR cultivars, and WUE was improved in both the IJHR and JIR cultivars, especially in the IJHR cultivars. Compared to the JIR cultivars, the IJHR cultivars were found to have improved agronomic and physiological performances under the AWSD irrigation regimen, such as a larger sink size, higher percentage of productive tillers, higher matter production ability during reproductive and ripening periods, larger root biomass, deeper root distribution and greater nonstructural carbohydrate (NSC) accumulation in the stem at heading, larger NSC remobilization from the stem, and higher root oxidation activity and leaf photosynthetic rates during ripening period. Improved agronomic and physiological traits contributed to an increase in WUE with less yield loss for IJHR cultivars under the AWSD irrigation regimen. Abstract : IJHR cultivars possess not only a greater yield potential under continue flooding (CF), but also better yield performance and higher WUE under AWSD.